Charles Miller Fisher - From a concentration camp to Massachusetts General Hospital (Ictus, 2020)
The biography of Charles Miller Fisher is presented in the History of Vascular Neurology section, as the first article published in the Ictus Magazine.
Keywords: Miller Fisher; History of Vascular Neurology; Biography